Biomechanical assessment of Kirschner wires integrated with a novel external fixation device for treatment of pediatric supracondylar humeral fracture: a finite element analysis - Lu, Yu-Hsin; Tai, Ching-Lung; Lee, Wei-Chun; Wang, Si-Yao; Mao, Chi-Yu; Yang, Wen-E.; Chang, Chia-Hsieh; Kao, Hsuan-Kai (Frontiers in Bioengineering and Biotechnology, 2024)
Background: Pediatric supracondylar humeral fractures present considerable surgical challenges due to the difficulty of achieving proper fracture alignment and stable fixation while avoiding injury to the ulnar nerve. This study assesses the biomechanical performance of a novel Kirschner wire (K-wire) fixation device (KFD), designed to enhance stability and reduce complications linked to traditional K-wire configurations.Methods: Using finite element analysis (FEA), we evaluated four fixation strategies for treatment of pediatric supracondylar humeral simple transverse fractures: crossed pin fixation, crossed pin fixation with KFD, two lateral pin fixation, and two lateral pin fixation with KFD, under various mechanical loads. The analysis focused on the stress and strain experienced by the K-wires at the fracture site during torsional and bending forces.Results: FEA revealed that the KFD significantly reduced the stress and strain on the K-wires in all configurations. In both crossed pin and two lateral pin fixation methods, the addition of the KFD showed lower stress and strain levels compared to setups without the KFD.Conclusion: This study demonstrates the potential of the KFD to enhance fracture stability and reduce mechanical stress at the fracture site, suggesting a promising improvement in the treatment of pediatric supracondylar humeral fractures. This innovation may contribute to safer and more reliable outcomes in pediatric orthopedic surgery.